Corporate Financial Performance and Tax Avoidance in High-Tech Industries - Meliani Mukti; Khairanis Yulita; Mochamad Chairul Ihsan (Universitas Pendidikan Indonesia, 2024)
This study investigated the correlation between tax avoidance, corporate financial performance, and high-tech industries (HTI) characteristics in publicly listed industries in Southeast Asia. The Generalized Least Square (GLS) was administered to test the hypotheses in 666 industry-years from 74 publicly listed industries in Southeast Asia from 2013-2021, including nine from Indonesia, 23 from Malaysia, 11 from Singapore, five from the Philippines, and 26 from Thailand. The results support all the hypotheses by showing a positive influence of corporate financial performance on tax avoidance and was found to be more vital for industries in high-tech industries. It suggested that high-performing sectors in Southeast Asia had more power to influence the political process for their benefit. Profitable high-tech companies are more likely than the industry to use tax system uncertainties to minimize their tax obligations. These results support political power hypotheses rather than political cost hypotheses. Moreover, political power was more pronounced in high-tech industries, which the government saw as more valuable. This study investigated different geographical areas that might be neglected by previous studies and industry characteristics suspected to contribute significantly to the strong effects of corporate financial performance on tax avoidance.